Team resilience building in response to co-founder exits - Preller, Rebecca; Breugst, Nicola; Patzelt, Holger; Dibbern, Rieke (Journal of Business Venturing, 2023)
Founding teams often experience the exit of co-founders. To develop theory about how founding teams deal with adversity emerging from the exit of one of their members, we take a team-resilience perspective and study the development of six founding teams. Our inductive model highlights how founding teams take different trajectories following team member exits, leading to different types of psychological closure, which impact the teams' resilience building. Our model also suggests how teams not engaging in distancing from the exit-related adversity experience additional adversity within the continuing team, eventually leading to team failure. Our findings challenge and extend extant studies on exits in founding teams and team resilience.